Silver nanoparticles synthesis mediated by new isolates of Bacillus spp., nanoparticle characterization and their activity against Bean Yellow Mosaic Virus and human pathogens - Elbeshehy, Essam K. F.; Elazzazy, Ahmed M.; Aggelis, George (Frontiers in Microbiology, 2015)
Extracellular agents produced by newly isolated bacterial strains were able to catalyze the synthesis of silver nanoparticles (AgNPs). The most effective isolates were identified as Bacillus pumilus, B. persicus and B. licheniformis using molecular identification. DLS analysis revealed that the AgNPs synthesized by the above strains were in the size range of 77-92 nm. TEM observations shown that the nanoparticles were coated with a capping agent, which was probably involved in nanoparticles stabilization allowing their perfect dispersion in aqueous solutions. FTIR analyses indicated the presence of proteins in the capping agent of the nanoparticles and suggested that the oxidation of hydroxyl groups of peptide hydrolysates (originated from the growth medium) is coupled to the reduction of silver ions. Energy Dispersive X-ray Spectroscopy confirmed the above results. The nanoparticles, especially those synthesized by B. licheniformis, were stable (zeta potential ranged from -16.6 to -21.3 mV) and showed an excellent in vitro antimicrobial activity against important human pathogens and a considerable antiviral activity against the Bean Yellow Mosaic Virus. The significance of the particular antiviral activity is highlighted, given the significant yield reduction in fava bean crops resulting from Bean Yellow Mosaic Virus infections, in many African countries.